Internet addiction among adolescents in Lebanon - Hawi, Nazir S. (Computers in human behavior, 2012)
► 4.2% Of the sample experienced significant problems due to Internet usage. ► The adolescents most vulnerable to Internet addiction were the youngest. ► Internet usage almost doubled on holidays at all addiction levels. ► Users’ interest in information and research dropped as Internet addition increased. ► There were fewer nonaddicted and more addicted public school students than expected. Internet addiction has been a subject of research since 1996. In step with this trend, this study aims to illuminate Internet addiction in Lebanon based on research evidence. The timing of this study coincides with the growing rate of penetration of Internet service across the country and with current plans to improve this service. This study investigates Internet usage among adolescents, who are the most vulnerable to Internet addiction in the population. Permission to access schools to conduct this research was obtained from the Ministry of Education and Higher Education. A web-based questionnaire was completed by 833 intermediate and secondary students from public and private schools. The questionnaire included items on demographic information and Internet usage and an Arabic version of Young’s Internet Addiction Test (YIAT). The results showed that 4.2% of the sample had significant problems. Furthermore, the more problematic Internet use (PIU) was, the less the Internet was used for information and research, and the more it was used for entertainment. PIU is driven by deficiency needs fuelled by the use of interactive applications. The more deficient the need, the greater the obsession with top-notch interactive applications, and the less frequent the usage of non-interactive applications.